2020
DOI: 10.1186/s13054-020-03330-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of venous Doppler to predict adverse kidney events in a general ICU cohort

Abstract: Background Changes in Doppler flow patterns of hepatic veins (HV), portal vein (PV) and intra-renal veins (RV) reflect right atrial pressure and venous congestion; the feasibility of obtaining these assessments and the clinical relevance of the findings is unknown in a general ICU population. This study compares the morphology of HV, PV and RV waveform abnormalities in prediction of major adverse kidney events at 30 days (MAKE30) in critically ill patients. Study design and methods We conducted a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 18 publications
1
82
1
Order By: Relevance
“…While VExUS will not likely provide much information on the need for fluid, it may provide stop points to fluid resuscitation and identify patients who are likely to tolerate and benefit from fluid removal. While the focus in fluid resuscitation has long been cardiac output or forward flow, the literature suggests strongly that venous congestion, as determined by CVP or by venous Doppler indices, will at a certain point offset the benefits of increasing said forward flow [4][5][6][7]16]. In fact, Vellinga et al, in studying the microcirculation, showed that a CVP above 12 actually resulted in a decreased tissue perfusion, and was associated with sluggish capillary flow which they termed "microcirculatory tamponade" [17].…”
Section: Discussionmentioning
confidence: 99%
“…While VExUS will not likely provide much information on the need for fluid, it may provide stop points to fluid resuscitation and identify patients who are likely to tolerate and benefit from fluid removal. While the focus in fluid resuscitation has long been cardiac output or forward flow, the literature suggests strongly that venous congestion, as determined by CVP or by venous Doppler indices, will at a certain point offset the benefits of increasing said forward flow [4][5][6][7]16]. In fact, Vellinga et al, in studying the microcirculation, showed that a CVP above 12 actually resulted in a decreased tissue perfusion, and was associated with sluggish capillary flow which they termed "microcirculatory tamponade" [17].…”
Section: Discussionmentioning
confidence: 99%
“…The method adopted for FUSIC HD -the venous excess ultrasound (VExUS) score (see 23 High venous pressures first manifest on ultrasound as IVC dilatation, then as flow abnormalities in the great veins when assessed with PW Doppler. 24 The hepatic vein, portal vein and renal veins are key targets for assessment. Figure 2 illustrates normal and abnormal venous Doppler patterns.…”
Section: Q10 Is There Venous Congestion?mentioning
confidence: 99%
“…Eventually, interstitial pressure exceeds arteriolar inflow. This effect is more prominent in encapsulated organs such as the kidneys (11), where increased venous pressure increases interstitial pressure leading to organ dysfunction and acute kidney injury (11,12). Patients in shock are particularly susceptible to kidney edema formation.…”
Section: Introductionmentioning
confidence: 99%
“…It often leads to pulmonary edema, which results in hypoxia and is frequently detected on plain x rays or oxygenation indicators like PaO2/FiO2. In contrast, identifying an increase in right atrial pressure is more challenging (12). Central venous pressure monitors and pulmonary artery catheters assess right atrial pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation